Integrating Micro and Macro Practice: An Evaluation of the Policy Advocacy Course. (3rd July 2021) - Schwartz-Tayri, Talia M.; Malka, Menny; Moshe-Grodofsky, Merav; Gilbert, Neil
ABSTRACT: Policy advocacy is a professional competency in the Council of Social Work Education's (CSWE) Educational Policy and Accreditation Standards. Therefore, preparing social work students to engage in political arenas is an integral part of social work education. This study presents an evaluation of the policy advocacy course using a pre/posttest research design ( N = 154), and examines the theoretical link between the course and the change in students' motivation to engage in policy advocacy activities. Findings indicate that students' motivation to engage in policy advocacy and traditional resources for policy advocacy increased after the course. Path analysis demonstrated the mechanism through which these increases were achieved. The study suggests that including comprehensive policy advocacy training in the professional socialization of future social workers is a promising approach to increasing their active engagement in policy advocacy and satisfying CSWE requirements.